Incidence of silent venous thromboembolism after total hip arthroplasty: A comparison of rivaroxaban and enoxaparin. (22nd July 2020) - Rahman, Wael A.; Habsa, Gamal H; Al-Mohrej, Omar A.; Hammad, Mohammed; Selim, Naser M.; Hammad, Akram
Propose: Total hip arthroplasty (THA) is associated with a significant risk of venous thromboembolism (VTE). Different thromboprophylaxis strategies have been used to prevent VTE. The primary aim of this study was to report the incidence of VTE and compare the efficacy and safety of rivaroxaban to enoxaparin. The secondary outcome was to report the incidence of silent deep venous thrombosis (DVT) using computed tomography venography. Methods: One hundred sixty patients who underwent THA were enrolled in a prospective study. Patients were randomized into two groups as follows: those who received rivaroxaban 10 mg oral daily (group RXE) and those who received enoxaparin 40 IU/day subcutaneously for 14 days (group ENO). Results: Both groups were matched for age, sex, comorbidities, special habits and preoperative laboratory investigations. The overall incidence of DVT was 5% ( n = 8), which included four patients clinically diagnosed as having DVT and four with silent DVT. All the DVT cases occurred in veins below the knee and in the group RXE; none of the cases occurred in group ENO ( p = 0.04). The incidence of DVT was significantly higher in patients with high body mass indexes ( p < 0.001), older age ( p = 0.024) and medical comorbidities ( p = 0.14). No mortality, pulmonary embolism, stroke, wound infection or major bleeding occurred in either group. Conclusions: Among the patients who underwent hip arthroplasty, rivaroxaban prophylaxis was found to be associated with lower efficacy and similar safety outcomes as compared with enoxaparin anticoagulants.